Artificial intelligence technology application and corporate ESG performance—evidence from national pilot zones for artificial intelligence innovation and application - Xie, Hanjin; Luo, Jiayi; Tan, Xi (Frontiers in Artificial Intelligence, 2025)
This study empirically examines the impact of artificial intelligence (AI) technology on corporate ESG performance using data from Chinese listed companies from 2011 to 2022 and a multi-period difference-in-differences (DID) model. The results reveal that AI significantly enhances overall corporate ESG performance by alleviating financing constraints, promoting green innovation, and strengthening information disclosure. These effects are particularly pronounced in the environmental (E) and governance (G) dimensions. Further analysis indicates that equity concentration, media attention, and data availability positively moderate the relationship between AI adoption and ESG performance. Based on these findings, this study suggests expanding AI application scenarios to facilitate the formulation of more targeted ESG strategies, deepen the integration of AI and ESG practices, and support high-quality economic development. The conclusions provide theoretical and empirical support for technology-driven corporate sustainable transformation.